OPTIMIZATION OF INVESTMENT RESOURCES DURING REPAIR OF POWER ENTERPRISE'S EQUIPMENT - A. Ievlev (Вестник университета, 2017)
The author presents an author's approach to the organization of the process of modeling equipment repair at enterprises of the power complex. The approach is based on the use of a modern network planning tool. It seems that the approach will increase the efficiency of using limited resources of energy companies.